"Corpus can be tricky": revisiting teacher attitudes towards corpus-aided language learning and teaching. Issue 7 (3rd September 2022) - Poole, Robert
Abstract: The present study explores the attitudes of novice teachers towards corpus-aided language learning and teaching in an undergraduate writing course for multilingual students at a large US public university. The participating instructors facilitated approximately 75 minutes of corpus training for their students and implemented 4-6 corpus activities over the course of the 16-week term. Participating instructors completed an initial survey documenting existing knowledge of, experiences with, and attitudes towards corpus-aided language learning and teaching, a second open-ended questionnaire at the mid-point of the academic term exploring their experiences, and a final instrument assessing how their attitudes had potentially evolved, either positively or negatively, and their likelihood for continued implementation of corpus-aided pedagogy in their classrooms. To offer a balanced perspective, data was also collected from three teachers who chose not to implement corpus activities in their courses. Findings display generally positive attitudes towards corpus study but also reveal emergent tensions regarding the use of ready-made corpus activities and the key affordances of discovery, authenticity, and autonomy often forwarded in support of corpus pedagogy.